PENGEMBANGAN UKBM DENGAN PENDEKATAN ENGINEERING DESIGN PROCESS (EDP) UNTUK MENINGKATKAN LITERASI STEM SISWA SMA - Indri Widiyanti; Pramudya Dwi Aristya Putra; Firdha Kusuma Ayu Anggraeni (Universitas Jember, 2021)
UKBM is a learning tool using the Semester Credit System (SKS) and is a small learning unit that is arranged sequentially by involving study time units. This research is focused on developing UKBM with the Engineering Design Process (EDP) approach in learning physics in high school. The purpose of this study was to produce a valid UKBM and determine the effectiveness of UKBM through increasing students' STEM literacy after using the EDP-based UKBM. This study uses a research and development (R&D) model with the ADDIE model consisting of five stages, namely: Analysis, Design, Development, Implementation and Evaluation. The results of the validity of product development are declared valid by the three validators with an average percentage of 88%, so that product development can be implemented in schools. The results of the effectiveness obtained from analyzing the results of the pre-test and post-test N-gain with the acquisition of N-Gain of 76.96% so that it is in the high category. The development of UKBM with the Engineering Design Process (EDP) Approach to improve STEM literacy of high school students was declared valid and effective.